Evaluasi dan Revisi Hukum Nasional Pasca-Intervensi Eksekutif: Analisis Urgensi Berdasarkan Prolegnas dan Implikasinya terhadap Moralitas Judikatif: Evaluation and Revision of National Laws Following Executive Intervention: An Analysis of Urgency Based on the National Legislation Program and Its Implications for Judicial Integrity - Aan Tirta Gandana; Agus Hendrayana; Dainsyah; Dian Amalia Dewi; Yuda Permana Sidiq; Imas Rosidawati Wiradirja; Deny Haspada (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2024)
This study examines two critical dimensions of Indonesia’s national legal reform: the urgency of overhauling the National Legislation Program (Prolegnas) following executive interventions during President Joko Widodo’s administration, and the implications of such interventions on judicial morality. Employing a qualitative comparative methodology, the research integrates document analysis of Prolegnas, draft laws, and government regulations, regulatory audits, and in-depth interviews with legislative and judicial stakeholders. Findings reveal that fragmented authority and the omnibus law approach without thorough audits generate legal uncertainty, while abrupt statutory revisions cause ethical dilemmas for judges and inconsistencies in legal interpretation. The study recommends embedding systematic regulatory audits, early involvement of the judicial council, establishing an independent ethics oversight body, and incorporating explicit judicial morality clauses in every legislative amendment. This integrated framework aims to ensure Prolegnas produces laws that are responsive, accountable, and substantively just.